2012
DOI: 10.1093/glycob/cws068
|View full text |Cite
|
Sign up to set email alerts
|

The essential endoplasmic reticulum chaperone Rot1 is required for protein N- and O-glycosylation in yeast

Abstract: Rot1 is an essential yeast protein originally shown to be implicated in such diverse processes such as β-1,6-glucan synthesis, actin cytoskeleton dynamics, or lysis of autophagic bodies. More recently also a role as a molecular chaperone has been discovered. Here we report that Rot1 interacts in a synthetic manner with Ost3, one of the nine subunits of the oligosaccharyltransferase complex, the key enzyme of N-glycosylation. Deletion of OST3 in the rot1-1 mutant causes a temperature sensitive phenotype as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Both types of glycosylation are initiated in the ER, O-mannosylation by distinct PMT complexes and N-glycosylation by the membrane protein complex OST [129]. Activity of both enzyme complexes depends on the essential ER chaperone Rot1 [130], and they can act on the same acceptor protein (e.g., [94][95][96]131]). It was shown that PMTs and OST compete for acceptor protein substrates, and that O-mannosylation can precede N-glycosylation, suggesting that PMTs have the potential to alter the number of N-linked glycans [96] (M.L.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of glycosylation are initiated in the ER, O-mannosylation by distinct PMT complexes and N-glycosylation by the membrane protein complex OST [129]. Activity of both enzyme complexes depends on the essential ER chaperone Rot1 [130], and they can act on the same acceptor protein (e.g., [94][95][96]131]). It was shown that PMTs and OST compete for acceptor protein substrates, and that O-mannosylation can precede N-glycosylation, suggesting that PMTs have the potential to alter the number of N-linked glycans [96] (M.L.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Rot1 was also found to be involved in the O-mannosylation process, as glycosylation of distinct glycoproteins of this type was affected as well. Altogether, it can be assumed that Rot1 acts also as a chaperone required to ensure proper glycosylation [38].…”
Section: Cell Wall Alteration Resulting From the Defect In Dolichol Amentioning
confidence: 99%
“…6). ROT1 encodes an essential chaperone required for N-and O-glycosylation in yeast 55 , and is required for normal levels of β-1,6-glucan 56 . Both KRE5 and BIG1 are also required for proper β-1,6 glucan synthesis 57,58 .…”
Section: Bionic Predictions Of Chemical-genetic Interactionsmentioning
confidence: 99%